Multilingualism and morality in statutory interpretation - Solan, Lawrence M. (Language and Law / Linguagem e Direito, 2017)
This article discusses some of the costs and benefits of multilingual legislation, focusing largely on Canada and the European Union. Courts interpreting these laws must take into account the different language versions, since each version is equally authoritative. Fidelity to the legislature’s will comes with very high stakes in this context, because multilingual legislative systems are most typically a means for recognizing the autonomy of minority groups, which, in exchange, cede some of that autonomy to a higher legal order. Thus, there is a special moral duty to ensure that the laws are construed faithfully at the same time that language barriers make it appear, at least on the surface, that it is more difficult to do so. Moreover, the risk of judges substituting their own values for those of the legislature when there is no single, definitive legal text, appears to become magnified in multilingual settings, creating the risk of decision making that would not stand up to moral scrutiny even in monolingual systems. This article argues that despite the apparent difficulties inherent in multilingual legislation, it actually reduces uncertainty in meaning by creating additional data points for statutory interpreters to consider. Multilingualism does, however, lead to certain additional problems of ambiguity. These, for the most part, however, are generally resolved fairly easily. It is further argued that the European approach to interpretation, which I call Augustinian Interpretation, is likely to lead to results more faithful to the legislature’s intent than is the standard Canadian approach, called the Shared Meaning Rule. Arguments from case law, from linguistics and from the philosophy of language are adduced to support these conclusions.